Pedicle screw sublaminary wiring (PSSW) combined with anti-tuberculosis chemotherapy for treating spinal tuberculosis in adults: A cohort study - Azharuddin, Abdul; Fajar, J. K. (UANL. Facultad de Medicina, 2016)
Operative procedures and anti-tuberculosis combinations are controversial for tuberculous spondylitis (TS) management in cases with risk of deformity, fragments, instability, and neurological disorders. Purpose: To assess the effectiveness of a combination of anti-tuberculosis and pedicle screw sublaminary wiring (PSSW) for treating TS. Method: This study was a cohort study with a pre-test/post-test control design. This study was conducted at the Dr. Zainoel Abidin Hospital (Banda Aceh) from March 2005 to March 2007. Sampling technique was judgement sampling. Neurological data deficit (Frankel classification) was analyzed before and after treatment using the Spearman test. Kyphosis angles were analyzed before and after treatment using the regression correlation test. Results: A total of 18 patients (61.1% male and 38.9% female) participated in this study. The spinal column involved in this study was 55.6% thoracic, 27.8% thoraco-lumbar, and 16.7% lumbar. Neurological status before the treatment was 11.1% Frankel C, 72.2% Frankel, D, and 16.7% Frankel E. Neurological status after the treatment was 5.55% Frankel C and 94.4% Frankel E. It showed that there was no significant association between a combination of anti-tuberculosis and PSSW for neurological deficit improvement (P = 0.212). The mean angle of kyphosis before the treatment was 23.05 ± 11.9 while after the treatment it was 10.5 ± 5.9. It showed that there was a significant association between a combination of anti-tuberculosis and PSSW for kyphosis degree improvement (P = 0.000). Conclusions: A combination of anti-tuberculosis and PSSW for six months provided significant results if assessed from degree of kyphosis, but did not provide significant results if assessed from Frankel classification.